Profile of sports section and sport journalism practice in Malaysian national newspaper: Focus on Malay language print media - Sarimah, I.; Hamedi, M.A. (2014)
Sports and society have a close relationship because they have elements of popular entertainment and leisure. Media is capable of translating popular sports information through the content of sports column. Most of newspapers in Malaysia have its own sport sections. Newspaper industry views sport space as a strategy and value added in' the newspaper setting for improving readership and circulation of their publications. Thus, the study shows the practice of sports journalism is very important to give strength to the newspaper sports column in Malaysia. This study focuses on sports journalism, print media in the Malay language in Malaysia with a focus on the sports content profile, the perception of sports editor, sports journalism practices, as well as factors and the importance of the publication of the newspaper sports column. Content analysis method was used to study the newspaper sports column from the two leading media organizations, namely Utusan Malaysia and Berita Harian. Media economic theory is used as the framework of study. The results show the prevailing imbalance of information published in the newspaper sports column. The news of international sports and overseas athletes are given more space than locals' local news in the Malaysian newspaper sports section. Advertisements are also found to have considerable influence on the newspaper sports section. The element of contiguity or proximity (events that occur close to the reader) is not a priority element in sports news. The study also found that in order to ensure the survival of newspapers through newspaper advertising revenues, the media would give priority to advertising space. The results reveal that sports section need to sacrifice space to advertisements, and this creates constraints on the sports news and information for publication. Qualitative findings showed that sports editors and journalists in Malaysia do not have an ethical sports journalism guidelines or codes of practice as being practiced in the West. Thus, the daily practice of ethics and practice are based on their own judgments and their 'professionalism as a media reporter. The study found that all newspaper editors believed that a sports section is a must in a newspaper due to its attraction and followers, which is capable of generating advertising revenue and increasing newspaper circulation. This study also shows that placement of news and articles of sport in the sport sections is based on the media economic fundamentals which focuses on . newspaper market and advertising revenue. Newspapers sport section has also succumbed to the modem theory of journalism as a result of the competition of the sports information through the advent of the new media.'